Anti‐inflammatory agents in the treatment of bipolar depression: a systematic review and meta‐analysis. (18th March 2016) - Rosenblat, Joshua D; Kakar, Ron; Berk, Michael; Kessing, Lars V; Vinberg, Maj; Baune, Bernhard T; Mansur, Rodrigo B; Brietzke, Elisa; Goldstein, Benjamin I; McIntyre, Roger S
Abstract : Objective: Inflammation has been implicated in the risk, pathophysiology, and progression of mood disorders and, as such, has become a target of interest in the treatment of bipolar disorder (BD). Therefore, the objective of the current qualitative and quantitative review was to determine the overall antidepressant effect of adjunctive anti‐inflammatory agents in the treatment of bipolar depression. Methods: Completed and ongoing clinical trials of anti‐inflammatory agents for BD published prior to 15 May 15 2015 were identified through searching the PubMed, Embase, PsychINFO, and Clinicaltrials.gov databases. Data from randomized controlled trials (RCTs) assessing the antidepressant effect of adjunctive mechanistically diverse anti‐inflammatory agents were pooled to determine standard mean differences (SMDs) compared with standard therapy alone. Results: Ten RCTs were identified for qualitative review. Eight RCTs (n = 312) assessing adjunctive nonsteroidal anti‐inflammatory drugs (n = 53), omega‐3 polyunsaturated fatty acids (n = 140), N ‐acetylcysteine (n = 76), and pioglitazone (n = 44) in the treatment of BD met the inclusion criteria for quantitative analysis. The overall effect size of adjunctive anti‐inflammatory agents on depressive symptoms was −0.40 (95% confidence interval −0.14 to −0.65, p = 0.002), indicative of a moderate and statistically significant antidepressant effect. The heterogeneity of the pooled sample was low ( I ² = 14%, p = 0.32). No manic/hypomanic induction or significant treatment‐emergent adverse events were reported. Conclusions: Overall, a moderate antidepressant effect was observed for adjunctive anti‐inflammatory agents compared with conventional therapy alone in the treatment of bipolar depression. The small number of studies, diversity of agents, and small sample sizes limited interpretation of the current analysis.